1997
DOI: 10.1046/j.1365-2427.1997.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally induced spatio‐temporal variations in the fecundity of brown trout Salmo trutta L.: trade‐offs between egg size and number

Abstract: 1. Resident brown trout Salmo trutta in the Esva River basin (north Spain) live in a patchy environment with tracts of riparian forest or meadow along stream banks. This study assessed whether the reproductive traits of brown trout from four contrasting sites reflected site‐specific factors. 2. Length at maturity (10.5–11 cm of 1 + individuals) was the same in the four sites examined but slowest growers in slow‐growing sub‐populations delayed maturity for 1 year relative to fast‐growing fish. The analysis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 34 publications
8
101
2
2
Order By: Relevance
“…Stronger relationships with the standard length were found for the farmed fish and correlations for the spawner weight were similar for both populations. Similar relationships of the reproductive parameters with the size of brood fish have been found by many authors (MCFADDEN et al, 1965;BAGENAL, 1969;OJANGUREN et al, 1996;L´ABÉE-LUND and HINDAR, 1990;LOBON-CERVIA et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Stronger relationships with the standard length were found for the farmed fish and correlations for the spawner weight were similar for both populations. Similar relationships of the reproductive parameters with the size of brood fish have been found by many authors (MCFADDEN et al, 1965;BAGENAL, 1969;OJANGUREN et al, 1996;L´ABÉE-LUND and HINDAR, 1990;LOBON-CERVIA et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study are consistent with the previous findings that, in salmonids, both egg size and fecundity correlate positively with maternal size (Fleming and Gross, 1990;Lobon-Cervia et al, 1997;Rollinson and Hutchings, 2010). Studies have shown that larger eggs give rise to larger juveniles, and that larger juveniles exhibit increased survival, competitive ability, swimming performance, growth and overall fitness (Blaxter, 1988).…”
Section: Size and Survivalsupporting
confidence: 93%
“…Several energy-related mechanisms can influence the amount of energy allocated to gonads during a reproductive cycle and thus the number and size or quality of eggs that are spawned (Van Winkle et al, 1997). Most studies addressing maternal provisioning and egg quality in fish consider various measures of egg and alevin size, such as diameter, wet mass, dry mass (e.g., Hutchings, 1991;Lobon-Cervia et al, 1997;Olofsson and Mosegaard, 1999;Berg et al, 2001;Hendry et al, 2001;Heinimaa and Heinimaa, 2004), the yolk mass and the yolk sphere diameter and volume (Heming and Buddington, 1988) and biochemical composition (Lahnsteiner et al, 1999;Keckeis et al, 2000;Berg et al, 2001;Yanes-Roca et al, 2009). Enzyme activity has been used less frequently as an indicator of egg quality (Lahnsteiner et al, 1999;Lahnsteiner et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that larger eggs may be an adaption to increased salinity in BW environments. There is a trade-off between egg size and fecundity: Fish that produce larger offspring lose in their overall fecundity and thereby in their potential maternal fitness (Smith and Fretwell 1974;Elgar 1990;Lobon-Cervia et al 1997). Because of that, either larger offspring (from larger eggs) must have greater fitness and survival in BW to compensate mother's greater energetic investment per offspring (coupled with loss in fecundity) or larger eggs are physiologically crucial at the certain embryonic developmental stages for successful reproduction in saline environment.…”
Section: Discussionmentioning
confidence: 99%